2006
DOI: 10.1134/s1068162006040054
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as effective protectors of urease from ultrasonic inactivation in solutions

Abstract: Inactivation of soybean urease in aqueous solution at pH 5.4, 36 degrees C, and high-frequency sonication (2.64 MHz, 1.0 W/cm2) is substantially reduced in the presence of seven structurally different flavonoids. A comparative kinetic study of the effect of these flavonoids on the effective first-order rate constants that characterize the total (thermal and ultrasonic) inactivation k(i), thermal inactivation k(i)*, and ultrasonic inactivation k(i)(US) of 25 nM enzyme solution was carried out. The dependences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Nar has an anti-cancer effect on esophageal cancer stem cell xenotransplanted tumor mouse models without altering the body and liver weight and the combination of Nar and doxorubicin can reduce the side effects of doxorubicin (29). Nar is both effective and safe as an anti-cancer drug (30). The present study found that Nar arrested SNU-1 cells in the G 0 /G 1 phase, promoting apoptosis in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 55%
“…Nar has an anti-cancer effect on esophageal cancer stem cell xenotransplanted tumor mouse models without altering the body and liver weight and the combination of Nar and doxorubicin can reduce the side effects of doxorubicin (29). Nar is both effective and safe as an anti-cancer drug (30). The present study found that Nar arrested SNU-1 cells in the G 0 /G 1 phase, promoting apoptosis in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 55%
“…It is noteworthy that depending on the specific operational conditions, the modification effect on enzyme molecules can be activation or inactivation. Generally speaking, a stable cavitation effect caused by mild ultrasonic conditions (i.e., low intensity and short time) can cause oscillating resonance bubbles to form microcurrents through the surrounding solution, thereby producing milder shear stress in the solution (Tarun et al., 2006). The mechanical effect at this level can modify the enzyme structure in a way that loosens its spatial conformation and increases the exposure of more active sites, and thereby improve the enzyme activity (Bashari et al., 2013a; Subhedar & Gogate, 2013).…”
Section: Protocols and Applications Of Ultrasound In Free Food Enzyme...mentioning
confidence: 99%
“…They established to have metal chelating effect, antioxidant, antidiabetic, antiviral, antiallergic, antiestrogenic, antimicrobial, ischemic heart disease adipolytic activity, anti-inflammatory, antiobesity, hypoxia, anti-cancer and hepatoprotective activity. Because of all these pharmacological action, both naringenin and naringin are assumed to be useful as a food supplement [41][42][43][44][45][46][47]. The accelerated death could be related to the interactions of Citrus reticulata components…”
Section: Acute Toxicity Of Cerastes Cerastes Venom and Its Reaction With Aqueous And Methanolic Citrus Reticulata Extracts And Antivenommentioning
confidence: 99%